Politiques territoriales et évolution des registres d’action de l’Etat au Maroc : une entrée par la logistique - Jean DEBRIE; Nora MAREÏ (L'Espace Politique, 2019)
The objective of this paper is to contribute to the reflections on the evolution of the role of the State in Morocco. We favour a reflection based on a specific economic sector, that of logistics. This logistical issue is considered in this research as the set of activities and operations that allow the transport of goods in and between urban areas. The analysis of a national logistics policy and the observation of the application of this policy around two metropolitan areas of the Moroccan area - Casablanca and Tangier - allows us to observe this recomposition of the role of the State in the development policies. This reflection is the result of exploratory research based on an analysis of public action documents and a field survey conducted in Casablanca and Tangier as well as in Rabat. On the one hand, it confirms the growing political importance of this logistical issue in the context of a strategy of integration into global networks. On the other hand, it allows a reading of this evolution of the State's roles between maintaining a strong central authority (through its agencies, operators and the control of local actors), ongoing decentralization and the increasing role of major economic operators. From a general point of view, this reflexion illustrates the contribution of logistics to the development of territories, particularly metropolitan areas.